Fungsi Manajemen Kelas dalam Pembentukan Karakter dan Motivasi Belajar Siswa - Muhammad Iqbal; Lu'luin Najwa; Nur Ihwani Hidayah (Realita : Jurnal Bimbingan dan Konseling, 2022)
This study aims to find out how the classroom management implemented and implicated in shaping students' character and learning motivation at MA Plus Nurul Islam Sekarbela. The research method used is descriptive qualitative. The subjects in this study were Mathematics subject teachers and class X students, totaling 54 students which were divided into 2 majors, namely Science and Religion majors. Data collection techniques used were observation, interviews and documentation. The results of the study reveal that: 1) The classroom management in shaping students' character and learning motivation at MA Plus Nurul Islam Sekarbela was implemented by mathematics teachers starting from managing the classroom environment, enforcing classroom discipline, controlling students' behavior, carrying out conflict management in the classroom. in the classroom, applying classroom management approaches, and doing literacy habits for 15 minutes. During the Covid-19 pandemic period, the teachers also made teaching materials in the form of PDF and PPT files, simulation videos or tutorials. The teachers also utilize Google Classroom application, Group WA and Telegram to convey information and interact and apply entertaining methods. 2) The implication of the implementation of classroom management in shaping the students’ character and learning motivation is that their character appears to be increasingly disciplined, independent, hard working and has a high curiosity. The students become more enthusiastic in participating in the learning process, do not give up easily, like to solve problems and are independent in completing assignments. Students look focused and enthusiastic during the learning process.